2017
DOI: 10.1177/1687814016689040
|View full text |Cite
|
Sign up to set email alerts
|

Bearing preload optimization for machine tool spindle by the influencing multiple parameters on the bearing performance

Abstract: The bearing preload plays an important role on the bearing performance, particularly the important characteristics of the bearing include bearing temperature increases, the bearing fatigue life, and ball skidding. Generally, the bearing preload contains the initial bearing preload and the thermal-induced bearing preload. Moreover, the bearing performance is closely related to machine tool accuracy. Obtaining an optimal bearing preload can improve the spindle work accuracy of machine tools. A method for determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The spindle system thermal error, with deviations, was generated by an FEA model, based on a model previously described in our laboratory 15 and Jiang and Mao. 16 The comparative results for the simulation versus empirically derived measurements in condition of spindle speed of 3000 r/min and an axial load of 800 N are presented in Figure 11, and the axial load 800 N is selected for limiting the ball skidding which is clarified in Dong et al 17 Normally, the Z direction thermal error should have the smallest slope, because the spindle system has absolute symmetry structure. However, it was observed that the parallel bearing installation misalignment has a greater influence on the spindle thermal error in the Z direction than in the X and Y directions.…”
Section: Simulation Experiment and Discussionmentioning
confidence: 99%
“…The spindle system thermal error, with deviations, was generated by an FEA model, based on a model previously described in our laboratory 15 and Jiang and Mao. 16 The comparative results for the simulation versus empirically derived measurements in condition of spindle speed of 3000 r/min and an axial load of 800 N are presented in Figure 11, and the axial load 800 N is selected for limiting the ball skidding which is clarified in Dong et al 17 Normally, the Z direction thermal error should have the smallest slope, because the spindle system has absolute symmetry structure. However, it was observed that the parallel bearing installation misalignment has a greater influence on the spindle thermal error in the Z direction than in the X and Y directions.…”
Section: Simulation Experiment and Discussionmentioning
confidence: 99%
“…By combining the bearing fatigue life model and the internal stress distribution model, Xu [47] optimized the preload based on multi-parameter criteria with respect to bearing life reliability condition, analyzed the rotation influence on internal stress distribution and contact angle variation, obtained the optimal preload by adjusting the reliability of the fatigue life model. Dong [54] proposed a complete calculation method to obtain the optimal preload, with impact factors such as bearing stiffness, temperature rise, fatigue life and ball sliding considered. Figure 9 [54] is the relationship between the optimal preload when the three factors acting simultaneously, where the bearing skidding is the [54] minimum boundary condition, the relationship between the initial preload and the fatigue life is the maximum boundary condition for preload computation.…”
Section: Optimal Preloadmentioning
confidence: 99%
“…Dong [54] proposed a complete calculation method to obtain the optimal preload, with impact factors such as bearing stiffness, temperature rise, fatigue life and ball sliding considered. Figure 9 [54] is the relationship between the optimal preload when the three factors acting simultaneously, where the bearing skidding is the [54] minimum boundary condition, the relationship between the initial preload and the fatigue life is the maximum boundary condition for preload computation.…”
Section: Optimal Preloadmentioning
confidence: 99%
“…Recently, considerable researches have been carried out to improve the vibration response characteristics of MMS. The effects of design variables or operation parameters on system dynamics response have been covered with the inclusive variety of researches [6][7][8][9][10][11][12]. These previous researches were focused on improving the dynamic performances of highspeed (HS) motorized spindle through optimizing the design factors.…”
Section: Introductionmentioning
confidence: 99%